TUGAS PERKEMBANGAN KELUARGA DAN KEPUASAN PERNIKAHAN PADA PASANGAN MENIKAH USIA MUDA - Tyas, Fatma Putri Sekaring; Herawati, Tin; Sunarti, Euis (Jurnal Ilmu Keluarga dan Konsumen, 2017)
This study aimed to analyze the effect of characteristics before married, family characteristics, family development task toward marital satisfaction. The study using designs a cross-sectional study and retrospective study. Location of the research was selected purposively in Cibatok Village 2, Ciaruteun Udik Village, Cibatok 1 Village and Cimanggu 2 Village, District Cibungbulang, Bogor. Sample of this research were intact families who marry at the early age (the wife age’s under 19 years old and husband’s age under 25 years old) with max five years length of marriage and first child. Respondents in this study were mothers with sampling technique was purposive sampling with a total of 60 people. Data were collected through interviews with using a questionnaire. Family development task in the medium category, and wife’s marital satisfaction in the low average. The results showed that the effect of family characteristics (long married, the income capita, age of wife) has a significant positive direct effect to family development tasks. Family development tasks has a significant positive direct effect to marital satisfaction. The family characteristics (long married, the income capita, age of wife) has a significant positive indirect effect to marital satisfaction.